2003
DOI: 10.1007/s00066-003-1044-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the iNOS Pathway in Inflammatory Macrophages by Low-Dose X-Irradiation In Vitro

Abstract: The inhibitory interference of low radiation doses with the iNOS pathway in inflammatory macrophages appears to be based on radiation effects on the translational and posttranslational control mechanisms of iNOS activity. However, contrary to our working hypothesis this is not related to radiation-induced induction of HO-1 expression and thereby increased degradation of heme which is essential for iNOS activity. Thus, other posttranslational modifications such as the proteasome degradation pathway might be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 26 publications
2
26
0
4
Order By: Relevance
“…Approximately 70% of the prescriptions of RT for benign diseases in German RT departments account for degenerative disorders [35], and annually, > 3,500 heel spur patients are treated in Germany [24]. Objective mechanisms influencing the intensity of inflammation and modulating the cell functions being responsible for the release and maintenance of the inflammatory reaction have been demonstrated by numerous in vitro [11,12,23,29,30,31] and in vivo studies [10,13,19,38]. The response rates of 87.7% obtained at 6-month follow-up in both of our study groups demonstrated an equivalent efficacy of the two different dose-fractionation schedules resulting in a highly significant improvement of the sum score.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 70% of the prescriptions of RT for benign diseases in German RT departments account for degenerative disorders [35], and annually, > 3,500 heel spur patients are treated in Germany [24]. Objective mechanisms influencing the intensity of inflammation and modulating the cell functions being responsible for the release and maintenance of the inflammatory reaction have been demonstrated by numerous in vitro [11,12,23,29,30,31] and in vivo studies [10,13,19,38]. The response rates of 87.7% obtained at 6-month follow-up in both of our study groups demonstrated an equivalent efficacy of the two different dose-fractionation schedules resulting in a highly significant improvement of the sum score.…”
Section: Discussionmentioning
confidence: 99%
“…Although not fully accepted in a variety of countries [35], LD-RT is reported to profoundly reduce the clinical symptoms of inflammatory disorders independently of the site of inflammation [21,31,34]. At the cellular level, LD-RT was found to suppress adhesion of peripheral blood mononuclear cells (PBMCs) to endothelial cells (ECs) [10,15,23], as well as the induction of reactive oxygen species (ROS) and inducible nitric oxide synthase (iNOS) in macrophages [9,11,27].…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro model, Hildebrandt et al showed that the NO production in stimulated macrophages could be significantly decreased by low single radiation doses between 0.3 and 2.0 Gy, whereas it was increased by doses > 2.5 Gy. The attenuated NO production lasted up to 30 h [5,6].…”
Section: Discussionmentioning
confidence: 99%